THE RECYCLING OF THE RUBBER WASTE BY INCORPORATION INTO THE CEMENT MATRICES - MODOI, Oana-Cristina; SÂRBU, Călin (Studia Universitatis Babeș-Bolyai Ambientum, 2017)
The rubber wastes result mainly from the automobiles, but may also result from the construction or from other industrial activities as well as from households. Increasing the use of the rubber has generated an increase of the amount of rubber waste resulted. Thus, the increasing of the amounts of the rubber waste produces important environmental issues, especially when they are stored. The degradation of the tires take long times, by comparison, we can even say that rubber wastes have an unlimited lifetime compared to other organic wastes. In addition, in the case of an accidental ignition of the stored tires, their combustion releases gases containing hazardous chemical compounds, and fine particles, into the environment. Some of that gases produced by ignition are dangerous not only for the environment but also for the human health. These are some of the reasons why the European legislation prohibited the storage of rubbers in the landfills. In this context, the recovery and the recycling of the rubber waste to the detriment of their storage become very important. This paper studies the possibility of the recycling of the rubber wastes by incorporating the crumbs of rubber in the cement. The rubber crumbs were added to the cement, partially replacing the fine aggregate in the cement matrix, in various proportions (10, 20, and 30% weight units). The characteristics of the resulting types of cement were evaluated from their mechanical and physical properties.